Browse in Africa: The current state of knowledge - Le Houerou, H.N. (International Livestock Centre for Africa, 1980)
The proceedings of a conference, reviewing current knowledge of browse species and their role in the development of livestock production. The papers cover the ecology of browse trees and shrubs, their geological distribution, relative palatibility for different animals, and composition and theoretical value. Also discussed are the primary and secondary production of browse, its intensification by economic and socially acceptable operations, browse regeneration management and research priorities.